Sources of Resistance to Colletotrichum lindemuthianum in the Secondary Gene Pool of Phaseolus vulgaris and in Crosses of Primary and Secondary Gene Pools - Mahuku, George S (Plant disease, 2002)
Use of genetic resistance is the most practical and economic way to manage anthracnose of common bean. Colletotrichum lindemuthianum, the causal agent of bean anthracnose, is a highly variabile pathogen, and there are no host resistance genes that are effective against all known races of the pathogen. To diversify sources of resistance, we screened the core collection of the secondary gene pool of Phaseolus spp. and interspecific lines derived from simple and complex crosses of primary and secondary genotypes for their resistance to anthracnose. High levels of resistance were observed in the secondary gene pool. None of the 162 accessions tested was susceptible to C. lindemuthianum. Of the two species composing the secondary gene pool, P. polyanthus displayed higher levels of resistance than P. coccineus, and all accessions tested were resistant. The response of P. coccineus was more variable, with six genotypes showing an intermediate reaction. Among the 75 lines from interspecific crosses, 49 were resistant to the three races (races 6, 15, and 3481) used in this study, and higher levels of resistance were found in lines that had P. polyanthus as one of the parents in the crosses than in the lines derived from P. coccineus. These lines constitute a valuable source of resistance and may aid in the development of stable resistance to anthracnose